Pemanfaatan Kecambah Kacang Hijau dan Kacang Kedelai sebagai Sumber Nitrogen pada Produksi Nata de Pina - Putriutami, Humaira Puspita; Marvie, Ilham; Fithriyani, Dina (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2024)
Pineapple skin, a by-product of the pineapple industry in Lampung, has significant potential for utilization. Pineapple peel extract can be used as a fermentation medium for nata de pina, thereby enhancing its added value. The production of nata de pina requires a nitrogen source that is safe for human consumption and poses no food safety risks. Legume sprouts, such as mung bean and soybean sprouts, have the potential to serve as nitrogen sources in the production of nata de pina. This study aimed to investigate the effect of varying concentrations of nitrogen sources from mung bean or soybean sprouts on the properties of nata de pina, including pH, total acidity, thickness, yield, moisture content, crude fiber, ash content, and sensory attributes (color, aroma, texture). Mung bean and soybean sprout juices were used at two concentration levels, 25% and 50% of the volume of pineapple peel juice (v/v). Data were analyzed using One-Way ANOVA with a 5% significance level, followed by DMRT if significant effects were observed. Nata de pina produced with the addition of 50% soybean juice demonstrated optimal results, with a thickness of 1.4 cm, yield of 67.5%, moisture content of 97.7%, crude fiber of 2.2%, and ash content of 0.16%. The sensory evaluation revealed scores of 4.26 for color (like), 2.92 for aroma (moderate), 3.78 for texture (like), and 3.78 for overall preference (like).